Optimalisasi Tambak Ikan Bandeng Non-Produktif dengan Budidaya Gracilaria Sp sebagai Solusi Kelangkaan Pupuk bagi Petani Tambak - Safir, Muhammad; Tahya, Akbar Marzuki; Serdiati, Novalina; Rusaini, Rusaini; Mangitung, Seftina Fifi (Jurnal Ilmiah Pangabdhi, 2024)
The enactment of PERMENTAN Number 10 of 2022 (Ministerial Regulation of Agriculture), which serves as a reference, indicates that pond farmers do not have the right to receive subsidized fertilizers. Additionally, the scarcity and rising prices of non-subsidized fertilizers in the market have led to a decrease in the productivity of fish and shrimp ponds, particularly those managed using conventional systems. This situation has also resulted in a decline in the income of the community as business actors. The objective of this community service activity is to provide guidance on cultivating Gracilaria sp. seaweed as one of the potential commodities that can be developed to maximize pond productivity. The socialization materials about seaweed Gracilaria sp. and its cultivation include preparation stages, seed spreading, monitoring, fertilization, harvesting, drying, storage in warehouses, and seaweed packaging. The results of this activity show the participants' enthusiasm to experiment with seaweed cultivation in one of the participants' ponds. Once it grows well, other farmers will begin to cultivate it. Farmers have understood about Gracilaria sp. seaweed and its cultivation, and they desire the realization and support of seaweed cultivation.